2021
DOI: 10.1186/s12893-021-01185-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgery for giant hepatic hemangioma

Abstract: Background The surgical indications for liver hemangioma remain unclear. Methods Data from 152 patients with hepatic hemangioma who underwent hepatectomy between 2004 and 2019 were retrospectively reviewed. We analyzed characteristics including tumor size, surgical parameters, and variables associated with Kasabach–Merritt syndrome and compared the outcomes of laparoscopic and open hepatectomy. Here, we describe surgical techniques for giant hepati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 54 publications
0
33
0
3
Order By: Relevance
“…Many studies have confirmed that hepatectomy and haemangioma enucleation are safe and feasible if the indications are properly controlled [ 2 , 5 , 7 , 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have confirmed that hepatectomy and haemangioma enucleation are safe and feasible if the indications are properly controlled [ 2 , 5 , 7 , 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hepatic haemangiomas larger than 5 cm were previously considered giant hepatic haemangiomas. However, recent studies have suggested that haemangiomas with a diameter greater than 10 cm should be considered giant hepatic haemangiomas [ 2 ], which is more consistent with the tumour characteristics and requirements for clinical diagnosis and treatment [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Although less invasive techniques, such as transarterial embolization of the feeding artery and radiofrequency ablation, could induce reduction of the size of giant HH, there is also evidence that surgical management is helpful for symptom relief and has low risk of mortality. 28 Orthotopic liver transplant represents an alternative treatment option in selected cases, with excellent outcomes in terms of safety and survival. 29 Given the low numbers of cases reported in the literature, it can be concluded that OLT in this setting constitutes an extremely rare indication.…”
Section: Hepatic Hemangiomamentioning
confidence: 99%
“…Management of patients with giant hemangiomas (GH) exceeding 10 cm in diameter is currently controversial. Despite prophylactic surgical treatment, historically advocated as the standard of care to avoid potentially life-threatening complications [ 3 ], the prevention of rupture alone is not considered a straightforward indication for surgical removal of an asymptomatic lesion [ 4 ], also taking into account potential postoperative complications.…”
Section: Introductionmentioning
confidence: 99%